'Dangerous Targets' revisited: Old dangers in new contexts plague marine protected areas. (September 2016) - Agardy, Tundi; Claudet, Joachim; Day, Jon C.
Abstract: The use of targets to provide measurable objectives and benchmarks for management, conservation, and restoration of ecosystems is commonplace. In the marine and coastal realms, targets have been successful in setting sustainable limits to fisheries harvests, thresholds for pollutants, and recommended amounts of representative habitat included in marine protected area (MPA) networks. Quantifiable targets can dissuade governments from making dubious claims about investments in ocean protection that sound impressive but cannot be verified. Examples are presented where protection targets have been used successfully for marine management, and instances where measurable and meaningful benchmarks serve to allow tracking of true progress. However, the setting of targets can also be a double‐edged sword. In some cases, targets have proven useful, but in many instances, interventions made to fulfil targets not only give a false illusion of progress or even success, they present opportunity costs that impede further conservation. Some of these issues were raised in the 2003 article 'Dangerous Targets?: Unresolved issues and ideological clashes around marine protected areas' that appeared in Aquatic Conservation : Marine and Freshwater Ecosystems . Since its publication, the article's warnings about how targets can sometimes be dangerous and counter‐productive have led to intense debate among scientists and policy‐makers alike, and the paper has been cited in more than 500 publications. Yet today, more than a dozen years after the first 'Dangerous Targets' publication, new targets are driving more MPA designations and conservation strategies than ever before, and the 'dangerous' aspects of target setting have been largely ignored. This paper discusses old 'dangers' in the context of new developments in marine conservation, including the lingering problem of having simplistic metrics drive marine policies, and the unintended result that can often occur when outputs (percentage of area under MPA designation) do not align with true outcomes of effective management and conservation. Newly emerging 'dangers' in letting areal targets (percentage of area under MPA designation) drive MPA designations are also discussed, including how the rush to fulfil obligations to protect a certain proportion of area is taking place in planning, separate from broader level, and potentially more holistic, marine spatial planning (MSP). The paper suggests five recommendations that would allow policy‐makers to use targets more effectively, including: (1) increase transparency in planning, especially around specific goals and objectives of MPA establishment; (2) use time‐based areal targets when representativity is a goal of the protected area strategy; (3) use MPAs when spatial protections are the best solution to the management challenge; (4) design MPAs with intrinsic performance goals, and use performance‐based metrics in subsequent evaluation of MPAs; and (5) embed MPA planning into broader policy frameworks, including MSP. These five recommendations are oriented toward multilateral institutions, governments, and non‐governmental organizations, suggesting concrete ways to utilize target‐setting to their best advantage, in order to fight the downward spiral of degradation affecting marine and coastal environments worldwide. Copyright © 2016 John Wiley & Sons, Ltd.